Acute Coronary Syndrome in Renal Transplant Recipients, A Retrospective Study - Muhammad Tassaduq Khan, Rashid Bin Hamid, Naranjan Lal, Sidrah Rashid, Beenish Hameed, Syeda Anam Shah, Tatheer Syed,; Muhammad Tassaduq Khan, Rashid Bin Hamid, Naranjan Lal, Sidrah Rashid, Beenish Hameed, Syeda Anam Shah, Tatheer Syed, (Pakistan Journal of Medical & Health Sciences, 2023)
Background:Acute coronary syndrome (ACS) is associated with instant decreased flow of blood to heart causing cardiac arrest in some cases. In renal transplantrecipients it is one of the major reasons for complications and death. Objectives:To determine the frequency of ACS in Renal Transplant Recipients (RTR). Methodology: This retrospective study was carried out at a public kidney center in which data of patients was included from 2017 to 2022. This included previously recorded data of 450 renal transplant recepients (RTR) from a public hospital over a period of five years.Patients between 15-70 years of age of either gender admitted for renal transplant patient were included in the study. Patients with pre-existing acute coronary syndrome or with incomplete data were excluded from the study. SPSS version 23.0 was used for data analysis. For qualitative variables, mean and standard deviation were reported while for quantitative variables, frequency and percentages were reported. Results: The findings showed that RTR were predominently male 342(76%) versus female 108(24%) from total of 450. Age wise middle aged patients were high in number 142 (31.56%). Acute Coronary Syndrome was reported in 15 (3.33%) patients. Death occured in 09 (1.86%) RTR patients of ACS. Readmission for up to 30 days were 83 (18.44%) patients, out of which 4 (4.82%) were for ACS, 3 (75%) for NSTEMI and 1 (25%) for STEMI. Conclusion: Based on this research findigs it is concluded that ACS in RTR is worth considering a problem. Keywords: Acute Coronary Syndrome, Renal Transplant Recipients, Renal Transplantation, Cardiovascular Event